2021
DOI: 10.3389/fnut.2021.706067
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of UPro as a New Nutrient on High-Quality Egg Production From the Perspective of Egg Properties, Intestinal Histomorphology, and Oviduct Function of Laying Hens

Abstract: This study was to investigate the effects of UPro as a new nutritive fortifier on high-quality egg production from the perspective of egg properties, intestinal histomorphology, and oviduct function of laying hens. Four hundred thirty-two Hy-Line Brown laying hens aged 56 weeks were allocated to four groups. Layers were given a basal diet or supplemented with different levels of small peptides (0.2, 0.4, and 0.8%) to replace soybean meal. After 1-week adaptation period, the feeding trial was conducted for 12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Reduced 1L-1 expression indicates a fewer number of macrophages, implying that the hens' health is suitable for producing high-quality eggs. Recent reports showed that diet supplementation such as phytogenic feed additive (67) and natural astaxanthin (68) improved intestine morphology, small organic peptide (18) and organic selenium (69) enhanced intestinal health while alfalfa meal (70) enhanced beneficial gut microbial population. Diets such as tea polyphenols at 600 mg/kg (71) and 400 mg/kg (72), and phytogenic extracts (73) have been found to enhance immune function capacity, while magnolol enhanced the antioxidant capacity of the ovary (74).…”
Section: Factors Affecting Albumen Quality Animal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced 1L-1 expression indicates a fewer number of macrophages, implying that the hens' health is suitable for producing high-quality eggs. Recent reports showed that diet supplementation such as phytogenic feed additive (67) and natural astaxanthin (68) improved intestine morphology, small organic peptide (18) and organic selenium (69) enhanced intestinal health while alfalfa meal (70) enhanced beneficial gut microbial population. Diets such as tea polyphenols at 600 mg/kg (71) and 400 mg/kg (72), and phytogenic extracts (73) have been found to enhance immune function capacity, while magnolol enhanced the antioxidant capacity of the ovary (74).…”
Section: Factors Affecting Albumen Quality Animal Healthmentioning
confidence: 99%
“…The use of natural-source feed such as natural products with antioxidant and antimicrobial properties derived from plants and animals are advantageous because they pose no residue effect, pollution, or toxicity risk. Natural products including antimicrobial peptides (16), purified amino acids from animal blood (17), small peptide synthesized from corn (18), prebiotics (19), probiotics (20), essential oil (21) and organic trace elements in the form of chelates or amino acid complexes (22) have been reported to influence albumen quality. The improvement in albumen quality with natural products are associated with their high bioavailability, antioxidant function and capacity to maintain gut microflora, which is important for animal health and bio-fortification of animal products.…”
Section: Introductionmentioning
confidence: 99%